ANALISIS NUTRISI PAKAN IKAN BERBAHAN BAKU CANGKANG KERANG SIMPING (Placuna placenta) - Nur Hikma; Tri Widayati Putri; Jawiana Saokani; Zul Khairiyah (Universitas Mataram, 2026)
This study aims to analyze the nutritional content of fish feed made from scallop shells (Placuna placenta) as an effort to utilize abundant fishery waste in the coastal areas of South Sulawesi. This study used a completely randomized design (CRD) with three treatments: 0%, 10%, and 20% scallop shell flour addition, each replicated three times. Parameters analyzed included moisture content, ash content, crude fiber, protein, and fat using the proximate test method. The results showed that the addition of scallop shell flour affected the nutritional composition of the feed. The sample with the addition of 20% scallop shell flour had a protein content of 38.09%, fat content of 9.31%, fiber content of 6.65%, moisture content of 8.00%, and ash content of 11.19%. All parameters met the quality standards for fish feed according to SNI 9043-4:2022.